BOOK REVIEW: Marina Soroka, “The Summer Capitals of Europe, 1814-1919”. Routledge, London and New York, 2017, viii, 342 p. ISBN: 978-0-415-79245-5 - MÂRZA, Radu (Studia Universitatis Babeș-Bolyai Historia, 2019)
Marina Soroka has solid knowledge of European nineteenth-century diplomacy and aristocracy, focusing on the Russian aristocracy and its ties with Europe. Over the last years she has published several books on the topic: Britain, Russia, and the road to the First World War. The fateful embassy of Count Aleksandr Benckendorff (1903-16) (Farnham, Surrey, England; Burlington, VT, Ashgate, 2011); Письма (1918-1940) к княгине А.А. Оболенской / Императрица Мария Федоровна, Великая княгиня Ольга Александровна, Великая княгиня Ксения Александровна. Edition by Marina Soroka (Moskva, Izdateľstvo im. Sabashnikovykh, Universitet Dmitriia Pozharskogo, 2013); in collaboration with Charles A. Ruud, Becoming a Romanov: Grand Duchess Elena of Russia and her world (1807-1873) (Farnham, Surrey, Ashgate, 2015). Her interest in the history of aristocracy, international relations, and last but not least her familiarity with important archival funds of Russian aristocratic families and with epistolary and memorialist sources, are some of the prerequisites of the present book.